Total Blood Lymphocyte Count Alteration During and after Pregnancy - Örgül, Gökçen; Soyak, Burcu; Portakal, Oytun; Beksaç, Meral; Beksaç, M. Sinan (Gynecology Obstetrics & Reproductive Medicine, 2017)
Objective: To investigate the impact of gestational changes on blood lymphocyte count in healthy pregnancies. Study Design: This retrospective study is consisted of 108 consecutive normal pregnancies who delivered at our department in December 2015. High-risk pregnancies with poor neonatal outcome and pregnancies with maternal disorders which may affect lymphocyte counts were excluded from the study. “Complete blood count” results of the patients were obtained from the computerized data base system of Hacettepe University Hospital. Blood samples of patients which were withdrawn a) prior to pregnancy (1-6 months before getting pregnant), b) during pregnancy (11-14th gestational weeks) and c) post-partum first day were used in this study. Results: The mean blood lymphocyte count was 2049.07 (±758.69) in patients before their pregnancies. The mean lymphocyte count decreased to 1850.93 and 1625 during pregnancy and after delivery respectively. A statistically significant decrease was found between three periods (before, during, and postpartum 1st day) (p:0.003). Conclusion: We have shown a significant decrease in total lymphocyte levels during pregnancy, consistent with the data presented in the literature. Pregnancy and related hormones have a negative impact on total blood lymphocyte level.